Some questions for learning about the environment and interpretative reading in Lithuanian schools (1918–1925) - Karčiauskienė, M. (Psichologija, 1964)
During the proletarian revolution (1918-1919 years) a fight took place between bourgeois training and scholasticism, for education and life relationships in Lithuanian schools. The native language has become important in primary education. Together with that, priority was given to the integrated teaching system: the native language was not the most important thing in school; the education policy surrounding environment of knowledge extraction out of the native language. The value of reading lessons that relate to environmental knowledge, wasn’t sufficiently assessed. This methodical direction also prevailed during the bourgeois dictatorship, but ideological familiarization with the surrounding environment fundamentals were different—bourgeois. As a result, in bourgeois Lithuania environmental knowledge issues were dissociated from the native language lessons system, and although some methodological advice received the attention, they generally did not constitute systems. Methodological interpretative reading guidelines have poorly addressed the question of reading lessons and environmental communications knowledge. Interpretative reading was little used in expanding children’s horizons.